Differential Longevity of Memory CD4 and CD8 T Cells in a Cohort of the Mothers With a History of ZIKV Infection and Their Children - Badolato-Corrêa, Jessica; Carvalho, Fabiana Rabe; Paiva, Iury Amancio; Familiar-Macedo, Débora; Dias, Helver Gonçalves; Pauvolid-Corrêa, Alex; Fernandes-Santos, Caroline; Lima, Monique da Rocha Queiroz; Gandini, Mariana; Silva, Andréa Alice; Baeta Cavalcanti, Silvia Maria; de Oliveira, Solange Artimos; et al. (Frontiers in Immunology, 2021)
Background: Zika virus (ZIKV) infection is responsible for mild and self-limiting disease in healthy adults. In newborns, it can occasionally lead to a spectrum of malformations, the congenital Zika syndrome (CZS). Thus, little is known if mothers and babies with a history of ZIKV infection were able to develop long-lasting T-cell immunity. To these issues, we measure the prevalence of ZIKV T-cell immunity in a cohort of mothers infected to the ZIKV during pregnancy in the 2016-2017 Zika outbreak, who gave birth to infants affected by neurological complications or asymptomatic ones. Results: Twenty-one mothers and 18 children were tested for IFN-γ ELISpot and T-cell responses for flow cytometry assays in response to ZIKV megapools (ZIKV MP). IFN-γ ELISpot responses to ZIKV MP showed an increased CD4 and CD8 T-cell responses in mothers compared to children. The degranulation activity and IFN-γ-producing CD4 T cells were detected in most mothers, and children, while in CD8 T-cells, low responses were detected in these study groups. Phenotypic analysis of the responding CD4 T cells for ZIKV CD4 MP revealed that the IFN-γ+ cells were mostly contained in the Temra memory T cell subsets. Conclusion: The imprint of the ZIKV specific T cell responses in pregnant mothers infected with ZIKV seems to be unrelated to their children's clinical outcome. Moreover, donors with a history of ZIKV infection demonstrated lasting ZIKV specific CD4 T cell immunity, but not for CD8 T cell. The consequence of a short-lived immunity of CD8 T cells for future ZIKV infections will be discussed.